Pengaruh Fintech, Teknologi Infromasi, Dan E-Commerce Terhadap Kepuasan Financial Masyarakat Kota Medan - Yola Yolanda; Dessyana Dessyana (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2022)
This study aims to examine and analyze the effect of fintech, information technology, and e-commerce on financial satisfaction both simultaneously and partially in the people of Medan City. The number of respondents as many as 400 people of Medan City. The sampling technique in this research is purposive sampling. The type of data in this study is primary data obtained through a questionnaire. The analytical tool used by the researcher is SPSS 25. The results of data analysis show that simultaneously the variables of fintech, information technology, and e-commerce, while partially the fintech and information technology variables affect the financial satisfaction of the Medan City community, while the e-commerce variable does not. affect the financial satisfaction of the people of Medan city. The value of Adjusted R Square (Adjusted R2) is 0.063 or 6.3%. So it can be said that fintech, information technology and e-commerce can explain financial satisfaction by 6.7% and the remaining 93.3% other variables not examined in this study.